Gold nanoparticles: synthesis, physiochemical properties and therapeutic applications in cancer. Issue 5 (May 2021) - Liu, Xin-Yu; Wang, Jing-Quan; Ashby, Charles R.; Zeng, Leli; Fan, Ying-Fang; Chen, Zhe-Sheng
Highlights: Gold nanoparticles (AuNPs) have been utilized in the treatment of various types of cancer. AuNPs have excellent photochemical and surface properties. The properties of AuNPs can be tuned by altering their size, shape or structure. AuNPs can be used to carry and enhance the action of chemotherapeutics. Abstract : Gold nanoparticles (AuNPs) have been shown to be useful as carriers of various anticancer drugs as well as diagnosis platforms. In this review, we discuss the synthesis and physiochemical properties of AuNPs. We also highlight the photothermal and photodynamic properties of AuNPs and relevant applications in therapeutic studies. Furthermore, we review the applications of AuNPs in cancer treatment as and their underlying anticancer mechanisms in multiple types of cancer.